Temperature influence on experimental analog behavior of MISHEMTs - Perina, Welder F.; Martino, Joao A.; Simoen, Eddy; Peralagu, Uthayasankaran; Collaert, Nadine; Agopian, Paula G.D. [UNESP] (Elsevier, 2025)
This work presents an analysis on experimental analog behavior of MISHEMTs operating in the temperature range from 450 K down to 200 K. The drain current (IDS) presented a slight anomaly, especially for temperatures lower than 400 K. In the transconductance it is possible to visualize a second peak, suggesting a second conduction. As shown, the transconductance presented a low dependence on gate length, and an anomaly was observed for the devices at 350 K. The output conductance and transistor efficiency behavior suggest a competition between the effects of the MOS and HEMT conductions, present in the device. A new kink was observed in the output characteristic (IDSxVDS) at room temperature, which is caused by the HEMT and MOS conductions interaction, and it is even more noticeable for higher overdrive voltages (VGT). This effect is called MISHEMT kink effect (MH-kink) in this work. The MH-kink shifts toward higher VDS for higher overdrive voltage, showing the stronger influence of the MOS conduction on the total drain current. The unity gain frequency (ft) increases from 800 MHz (450 K) to 1.8 GHz (200 K), while the AV goes in opposite direction from 43 dB (450 K) to 38 dB (200 K). Considering that the intrinsic voltage gain is good enough even at low temperatures, the MISHEMT can be identified as a good candidate for analog applications.